PEMECAHAN MASALAH LIMBAH LAUNDRY DI SLEMAN DENGAN PROGRAM IPTEK BAGI MASYARAKAT (IbM) - Aminatun, Tien; Padmaningrum, Regina Tutik; Yuliati, - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
Karangmalang and Kuningan are the area located near the campus ofYogyakarta State University and Gadjah Mada University. This causes the twoareas have crowded population. Many students from outside of Sleman Yogyakarta stay in many boarding houses that need laundry service since they do not have enough time and are very busy of studying activities. There are approximately 30 laundry service businesses in these areas. The condition has positive impact on local people income generating. However, it also cause adverse effects on the environment because of the laundry waste water directly discharged into the environment without prior treatment. The priority problem to solve is the disposal of waste water and dissemination of eco-friendly detergen. We had "Sekar Laundry" and "Ramadhani Laundry"as our partners in this programme. To achieve the objectives of the project we carried out the following methods: (1) socialization, counseling, and training for the introduction of ecofriendly detergents and simple sewage treatment; and (2) the application of appropriate technology of waste water treatment based on fitoremediation for both partners. The results obtained were in accordance with the purposes. We could overcome the environmental pollution caused by waste water of laundry activities. Based on laboratory tests, laundry waste water from the outlet of the Waste Water Treatment Plant (the WWTP) had significantly quality improvement that it made safer to be discharged into the environment, with 27,125% of BOD decline efficiency, 120,350% of COD decline efficiency, 17,300% of TSS decline efficiency, 11,597% of detergent decline efficiency, and 88% of phosphate decline efficiency